Variations of SOC and MBC observed in an incubated brown loam soil managed under different tillage systems for 12 years. (8th May 2019) - Li, Xiaosha; Han, Huifang; Ning, Tangyuan; Shen, Ying; Lal, Rattal
Abstract: To assess changes in organic carbon pools, an incubation experiment was conducted under different temperatures and field moisture capacity (FMC) on a brown loam soil from three tillage practices used for 12 years: no‐till (NT), subsoiling (ST) and conventional tillage (CT). Total microbial respiration was measured for incubated soil with and without the input of straw. Results indicated that soil organic carbon (SOC) and microbial biomass carbon (MBC) under ST, NT and CT was higher in soil with straw input than that without, while the microbial quotient (MQ or MBC: SOC) and metabolic quotient (qCO2 ) content under CT followed the opposite trend. Lower temperature, lower moisture and with straw input contributed to the increases in SOC concentration, especially under NT and ST systems. The SOC concentrations under ST, with temperatures of 30 and 35°C after incubation at 55% FMC, were greater than those under CT by 28.4% and 30.6%, respectively. The increase in MBC was highest at 35°C for 55%, 65% and 75% FMC; in soil under ST, MBC was greater than that under CT by 199.3%, 50.7% and 23.8%, respectively. At 30°C, the lower qCO2 was obtained in soil incubated under NT and ST. The highest MQ among three tillage practices was measured under ST at 55% FMC, NT at 65% FMC and CT at 75% FMC with straw input. These data indicate the benefits of enhancing the MQ; the low FMC was beneficial to ST treatment. Under higher temperature and drought stress conditions, the adaptive capacity of ST and NT is better than that of CT.